Earmarked Paternity Leave and the Relative Income within Couples - Jeppe Druedahl; Mette Ejrnæs; Thomas H. Jørgensen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
We study the causal link between earmarked paternity leave policies and the relative income share of women within couples. We utilize high quality administrative longitudinal register data for the universe of Danish individuals with a reform in 1998, which increased the earmarked paternity leave of fathers from two to four weeks. We estimate that the reform increased the women's intra-household share of labor income with around 1.2 percentage points in the years following childbirth. We estimate a significant increase up to seven years after childbirth. We furthermore find that the effect is primarily driven by women employed in the private sector.
Keywords: D63; H24; H31; J13; J16; J24; J78; 330; Income Share; Parental Leave; Earmarked Leave; Household Bargaining